Recent Advances in Asymmetric Wettability Dressings for Wound Exudate Management - Fang Wang; Wenqing He; Bing Dai; Xueji Zhang; Yongqiang Wen (Research)
The management of wound exudate is of vital importance for wound healing. Exudate accumulation around wound prolongs inflammation and hinders healing. Although traditional dressings can absorb wound exudate, they are unable to drain exudate in time, often resulting in a poor feature with wound healing. In recent years, the appearance of asymmetric wettability dressings has shown great potential in exudate management. Here, we summarize the latest progress of 3 kinds of asymmetric wettability wound dressings in exudate management, including Janus structure, sandwich structure, and gradient structure. The most common Janus structural dressing among asymmetric wettability dressings is highlighted from 2 aspects: single-layer modified Janus structure and double-layer Janus structure. The challenges faced by asymmetric wettability wound dressings are discussed, and the developing trends of smart wound dressings in this field are prospected.